Cognitive Leisure and Cognitive Reserve in Multiple Sclerosis Patients - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
The effect of cognitive leisure (eg reading books, playing cards etc) on prevention of cognitive impairment was studied in 36 adults (31 women) with MS treated at Kessler Research Center, West Orange, New Jersey Medical School, and Teachers College, Columbia University, NY, NY.